2020
DOI: 10.1177/1178638820909329
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Intervention Reduces Added Sugar Intake Among Baltimore Public Housing Residents: A Feasibility Study

Abstract: Public housing residents have high intake of added sugars, which is associated with sugar-sweetened beverage (SSB) consumption in their social networks. In this feasibility study, we designed and tested a network-oriented intervention to decrease added sugar intake by encouraging reduced SSB consumption. We conducted a 6-month single-arm trial testing a small-group curriculum (9 sessions) that combined behavior change strategies to reduce added sugar intake by promoting SSB reduction with a peer outreach appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…An example of how to implement such a program comes from a feasibility study in the health domain. Gudzune et al [29] successfully implemented a six-week program to decrease sugar intake among public housing residents, utilizing peer educators and social network helpers. Findings showed a significant decrease in sugar intake in peer educators and their networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of how to implement such a program comes from a feasibility study in the health domain. Gudzune et al [29] successfully implemented a six-week program to decrease sugar intake among public housing residents, utilizing peer educators and social network helpers. Findings showed a significant decrease in sugar intake in peer educators and their networks.…”
Section: Discussionmentioning
confidence: 99%
“…This research literature can be divided into several strands. The largest strand of research focusses on the influence of social networks on unhealthy food and drink consumption practices and related health issues; such as alcohol consumption [28], sugar intake [29], or obesity [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such networks, one would expect that low-threshold behavior change (e.g., eating at fast food restaurants) might propagate quickly from one person to the next, but that these same networks would remain refractory to changing high-threshold behaviors (e.g., cooking healthy food at home) due to social norms causing inertia ( Centola, 2018 ). A recent pilot study demonstrated how a social network intervention among public housing residents significantly reduced sugar-sweetened beverage intake, a low-threshold behavior ( Gudzune et al, 2020 ). Furthermore, our findings suggest that diffusion of a behavioral intervention in this population may occur less readily between neighbors compared to individuals outside the public housing development, and a geographically targeted behavior change intervention may also need to promote neighborhood cohesion to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Companies currently have a policy of genetic testing of products to determine and prevent bad lifestyles in consumption of certain products and prevent disease (Gudzune et al, 2020) due to the consumption of harmful products that has a direct relationship with consumers, for which the implementation of social networks with informative programs on health and nutrition will help to reduce consumption of these, this factor of consumerism significantly influences the healthy lifestyle and all social factors (Barros-Bastidas & Turpo, 2020;Malin et al, 2020). The labor sector as the center of studies is a key point to motivate and encourage a good healthy lifestyle, whose training by physicians and occupational health nurses will achieve significant effects for the welfare of human health, because food education is of utmost importance since at home food is consumed only by parents in a traditional way and not in a balanced way, for this reason there is obesity at an early age, so the intervention of health professionals is needed to motivate a good lifestyle (Upadhyaya et al, 2020).…”
Section: Impact Of the Post Pandemic On College Student' Lifestylesmentioning
confidence: 99%